2017
DOI: 10.1186/s12882-017-0601-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of rutin supplementation against cisplatin-induced Nephrotoxicity in rats

Abstract: BackgroundCisplatin (CP) is commonly used in the treatment of different types of cancer but nephrotoxicity has been a major limiting factor. Therefore, the present study aimed to study the possible protective effect of rutin against nephrotoxicity induced by cisplatin in rats.MethodsForty male Wistar albino rats were randomly divided into 4 groups. Rats of group 1 control group intraperitoneal (i.p.) received 2.5 ml/kg, group 2 CP group received single dose 5 mg/kg cisplatin i.p. group 3 rutin group orally rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 70 publications
11
54
0
Order By: Relevance
“…Also emodin which is found in rheum genus has nephroprotective effects against metals by inhibition of proliferation of renal mesangial cells (MSCs) and thus lower cellular DNA [25]. In addition, rutin as an active ingredient in rheum genus [26] showed nephroprotective effect against cisplatin [27] and hexachlorobutadien [6]. Isolated anthraquinones from rheum genus revealed protective effects against mercuric chloride in rats [28].…”
Section: Discussionmentioning
confidence: 99%
“…Also emodin which is found in rheum genus has nephroprotective effects against metals by inhibition of proliferation of renal mesangial cells (MSCs) and thus lower cellular DNA [25]. In addition, rutin as an active ingredient in rheum genus [26] showed nephroprotective effect against cisplatin [27] and hexachlorobutadien [6]. Isolated anthraquinones from rheum genus revealed protective effects against mercuric chloride in rats [28].…”
Section: Discussionmentioning
confidence: 99%
“…Hesperidin treatment showed renoprotective effect against gentamicin and this effect may be due to its antioxidant properties [96] . Nephroprotective effect of rutin indicated by study showed rutin administration attenuated cisplatin-induced alteration changes in the kidney [97] . carcinoma.…”
Section: Catalase Is a Hemoprotein And It Protects Cells From The Accmentioning
confidence: 98%
“…The elevated serum creatinine and BUN levels induced by cisplatin were significantly restored to their normal levels as in control group by rutin. The rutin protective effect against nephrotoxicity can be attributed to its antioxidant and anti-inflammatory effect on ROS and some cytokines may be involved in the glomerular filtration rate damage [86] . LDH , a cytoplasmic marker enzyme is a known indicator of the cell and tissue damage by toxic compounds [87] .…”
Section: Catalase Is a Hemoprotein And It Protects Cells From The Accmentioning
confidence: 99%
“…Rutin is a flavonoid with many pharmaceutical effects: antioxidant (Casa et al, 2000), antiinflammatory, antiviral, antibacterial, antitumor, antialergic, antithrombotic (Janbaz et al, 2002), hypolipidic, cytoprotective, (Yang et al, 2008) and antiulcer (Casa et al, 2000). Rutin reduces the toxicity caused by paracetamol and CCl4 in the liver, (Janbaz et al, 2002) and in Cisplatin treatment, the antioxidant activity explains the nephroprotective effects (Alhoshani et al, 2017) the present study aimed to study the possible protective effect of rutin against nephrotoxicity induced by cisplatin in rats. METHODS Forty male Wistar albino rats were randomly divided into 4 groups.…”
Section: Resultsmentioning
confidence: 96%